Students’ Perceptions of Listening Strategies in EFL Classrooms: A Qualitative Study - Nuna, Muhammad Andika; Luwiti, Sri Rumiyatiningsih; Umar, Irmawaty (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Listening is a fundamental skill that learners of English as a Foreign Language (EFL) must master. Without adequate listening proficiency, students are likely to experience frequent misunderstandings and rely on uncertain assumptions. However, developing effective listening skills often poses challenges for EFL learners due to various factors. This study aims to explore and describe students’ perceptions of listening strategies in the classroom. Employing a qualitative design, the research involved English Education students from Gorontalo State University, class of 2021, who achieved the highest scores in listening courses. Participants were selected through purposive sampling. Data were collected through interviews and analyzed using thematic analysis to identify recurring patterns and provide an interpretive account of the phenomena. The findings highlight the effectiveness of note-taking as a means of organizing information and the benefits of the pause-and-repeat strategy in clarifying comprehension. The study concludes that the implementation of listening strategies in classroom contexts is highly effective, as teachers’ use of both bottom-up and top-down processing facilitates students’ understanding of course materials through diverse cognitive processes. The study recommends that educators apply these strategies to enhance listening instruction, while future researchers are encouraged to further investigate their application in broader contexts.